Evaluation of Health Hazard and Governance Performance of Air Pollution: A Case Study of Z City - Ying Cui; Yunxia Shi (Frontiers Media S.A., 2022)
Based on the date of the main pollutant discharge and the change of pollutant concentration in Z city, this study performed the statistical analysis of the concentration data in excel. The data covers 3 years from 1 January 2015 to 31 December 2017. An exposure-response relationship model was used established to evaluate the health hazards caused by air pollution and the corresponding economic losses, further analyzing the relationship between air pollution, health hazards, and economic benefits. The results of the study showed that the changes in SO2 and NO2 concentrations in Z City from 2015 to 2017 have a great influence on the mortality rate of the local population, respiratory mortality, the rate of internal medicine of outpatients, and the rate of chronic bronchitis disease. The economic losses between 2015 and 2017 caused by PM10, the primary pollutant in the air, were 3.9 billion, 3.5 billion, and 2.9 billion respectively, accounting for 3.60%, 2.88%, and 2.09% of Z City's GDP, which were enormous. Finally, countermeasures of feasible treatment and in government performance were put forward.